Cardiotoxicity of lung cancer-related immunotherapy versus chemotherapy: a systematic review and network meta-analysis of randomized controlled trials - Jin, Chengwei; Qi, Jia; Wang, Qilei; Pu, Chenwei; Tan, Mingming (Frontiers in Oncology, 2023)
Background Previous clinical randomized controlled trials (RCTs) have demonstrated that immune checkpoint inhibitors (ICIs) cause various toxicities during cancer treatment, but the effects of different inhibitors in combination with chemotherapy for cardiotoxicity remain controversial. The aim of the present study was to assess cardiotoxicity caused by programmed cell death protein 1 (PD-1), programmed cell death-Ligand 1 (PD-L1), and cytotoxic T lymphocyte associate protein-4 (CTLA-4) in combination with chemotherapy to treat lung cancer. Methods The following ICIs were included in the present study: durvalumab, avelumab, ipilimumab, atezolizumab, pembrolizumab, cemiplimab, and nivolumab. The relevant information was extracted using a predefined data extraction table, and the risk of bias was assessed in randomized controlled trials using the Cochrane Bias Risk tool. The main outcomes were hypertension, heart failure, pericardial effusion, and other adverse cardiac events. The random effects model was used to conduct a paired meta-analysis, and a random effects network meta-analysis was then performed within a Bayesian framework. Results In total, 17 RCTs were included in the present study. There were 11,063 individuals in the experimental and control groups, with an average age greater than 60 years. Based on the evaluation of all drug classes in RCTs, CTLA-4+chemotherapy (RR, -0.69 [95% CI, 2.91-1.52] and PD-L1 (RR, -0.21 [95% CI, -1.03-0.60]) were less cardiotoxic than the control arm, which indicated they were safer options for adverse cardiac events. PD-L1 alone was less cardiotoxic than PD-1 alone (RR, -0.57 [95% CI, -1.96-0.82]). Further, the dual immunotarget inhibitor, PD-1+CTLA-4, had the lowest SUCRA value and had the highest cardiotoxicity (SUCRA=9). Conclusion When classified according to drug type, CTLA-4+chemotherapy is associated with fewer cardiac adverse events compared to other treatments. Dual immunotarget inhibitors are more likely to have adverse cardiac reactions. Therefore, clinicians should consider this evidence when developing an ICI immunotherapy regimen for lung cancer. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42023360931.